A case of encapsulating peritoneal sclerosis in a patient with chronic schistosomiasis - Fragkou, Paraskevi C. (IDCases, 2021)
Encapsulating peritoneal sclerosis (EPS) is a debilitating condition, mainly associated with long-term peritoneal dialysis, where up-regulation of intra-abdominal inflammatory pathways leads to a fibrocollagenous peritoneal membrane formation resembling a cocoon. EPS causes intestinal encapsulation leading to bowel obstruction and dilatation. Chronic schistosomiasis is characterized by dysregulation of pro-inflammatory and anti-inflammatory cytokines. EPS has never been reported before in patients with chronic schistosomiasis. We report the first, to our knowledge, case of a 57-year-old male originated from Burkina Faso with chronic intestinal and urogenital schistosomiasis and EPS. Although causality cannot be established solely by this case, we hypothesize that EPS may be the result of chronic inflammatory activation, due to immune dysregulation driven by chronic schistosomiasis. The potential pathogenetic linkage between these two conditions should be further explored.